1973
DOI: 10.1111/j.1476-5381.1973.tb08243.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5‐hydroxytryptamine in ketamine‐induced hypothermia in the rat

Abstract: Summary1. Intraperitoneal injection of graded doses of ketamine produced a dosedependent fall in body temperature of rats. Similarly, intracerebral injection of much smaller doses produced hypothermia. 2. Pretreatment of the rats with p-chlorophenylalanine (PCPA) greatly attenuated the hypothermic response to ketamine whereas the intraperitoneal injection of 5-hydroxytryptophan in PCPA-treated rats restored the hypothermic effect of ketamine. 3. Depletion of the brain monoamines by reserpine completely prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Consistent with many previous studies, we found in that ketamine dose-dependently induces hypothermia (Fahim et al, 1973; Garami et al, 2017; Schmitz et al, 2016). Furthermore, we found that mice do not become tolerant to this effect of ketamine over the course of three injections spaced at once per week.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with many previous studies, we found in that ketamine dose-dependently induces hypothermia (Fahim et al, 1973; Garami et al, 2017; Schmitz et al, 2016). Furthermore, we found that mice do not become tolerant to this effect of ketamine over the course of three injections spaced at once per week.…”
Section: Discussionsupporting
confidence: 93%
“…These findings led us to the hypothesis that the activation of 5-HT 2 receptors may attenuate AIH. In the present study, we use the injectable anesthetic ketamine to assess this hypothesis because 1) its dosing can be readily controlled because it is injected rather than inhaled, 2) it is well known to induce dose-dependent hypothermia in several species (Fahim et al, 1973; Garami et al, 2017; Schmitz et al, 2016), and the role of serotonin and specific serotonin receptors in ketamine-induced hypothermia remains controversial (Fahim et al, 1973). However, it is important to note that the use of ketamine as an anesthetic in humans is limited to specific cases such as hemorrhagic shock, hemodynamic instability, and bronchodilation (Kurdi et al, 2014), in contrast to its more extensive use as a veterinary anesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…2 h after lights turned on). It should be noted that both substances, ketamine and xylazine, evoke hypothermia in rodents [ 57 , 58 ], which in turn triggers building of high and complex nests to decrease the amount of radiated heat and, thus, alleviate thermal discomfort [ 59 ]. In our previous study, we found that neither single nor repeated anesthesia with isoflurane impaired nest scores [ 4 ] obtained by using the same nesting protocol [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, activations of the medial orbitofrontal cortex and ventral striatum were associated with improvements of overall depression scores as measured by the MADRS scores, while activation of the dorsal anterior cingulate cortex, extending into the pregenual cingulate/callosal region was associated specifically with the anti-anhedonia effects of ketamine, as measured using the Snaith-Hamilton pleasure scale (SHAPS), The SHAPS is a validated 14-item, self-administered scale that measures levels of anticipatory anhedonia (Leventhal et al, 2006 ; Franken et al, 2007 ; Nakonezny et al, 2010 ). Interestingly, the ability of ketamine to induce thermoregulatory cooling in animals (Fahim et al, 1973 ; Pietersen et al, 2006 ), resulting in reduced core body temperature, was a primary consideration in selection of ketamine for initial clinical studies for the off-label use of ketamine for treatment of children with pediatric bipolar disorder/fear of harm phenotype (Papolos et al, 2013 ), who appear to suffer from an inability to dissipate heat (Papolos et al, 2009 ). These findings suggest that WBH and ketamine, which both have strong thermoregulatory cooling effects, may activate the same positive affective or anti-anhedonic circuits, and that activation of these circuits, particularly the dorsal anterior cingulate cortex/pregenual cingulate cortex, may play a role in the anti-anhedonic effects.…”
Section: Putting Embodied Perspectives To Work: Exploring the Antidepmentioning
confidence: 99%